Distributed parameter model-based control of water activity and concentration of reactants in a polymer electrolyte membrane fuel cell. (19th October 2017) - Sarmiento-Carnevali, Maria; Serra, Maria; Batlle, Carles
Abstract: Water management is still a key challenge for optimal performance and durability of polymer electrolyte membrane (PEM) fuel cells. Water levels along the channel in a PEM fuel cell present important spatial variations that should be taken into account to avoid both local flooding and local drying. In this work, a decentralised model predictive control scheme is designed to maintain the water activity on both anode and cathode sides of the PEM at appropriate levels. The proposed strategy tackles the accumulation of liquid water on the surface of the catalyst layers, and the possibility of local drying, by controlling observed water activity spatial profiles. Classic PEM fuel cell issues like reactant starvation are also considered. High control performance is achieved. The strategy is applied to a validated distributed parameter PEM fuel cell model. Results show increased cell power density in comparison to non-spatial control strategies. Highlights: A novel control strategy for PEM fuel cell water management is proposed. Spatial profiles of water activity in the catalyst layers are controlled. Target water activity setpoint achieved through optimal humidification of reactants. A variation of the control strategy tackles reactant starvation. Results show increased performance in comparison to non-spatial control strategies.